2020
DOI: 10.3389/fimmu.2020.01192
|View full text |Cite
|
Sign up to set email alerts
|

Behçet's Disease Under Microbiotic Surveillance? A Combined Analysis of Two Cohorts of Behçet's Disease Patients

Abstract: Background: In Behçet's disease (BD), an auto-inflammatory vasculitis, an unbalanced gut microbiota can contribute to pro-inflammatory reactions. In separate studies, distinct pro-and anti-inflammatory bacteria associated with BD have been identified. Methods: To establish disease-associated determinants, we performed gut microbiome profiling in BD patients from the Netherlands (n = 19) and Italy (n = 13), matched healthy controls (HC) from the Netherlands (n = 17) and Italy (n = 15) and oral microbiome profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…and reduced presence of IgA-coated Erysipelotrichaceae spp. in the Dutch BD cohort compared to healthy controls, although this was not analyzed in the Italian cohort (14). These data support the requirement for more, larger studies to determine the geographical and environmental changes compared to disease-induced changes in the BD gut microbiome.…”
Section: Gut and Oral Microbiomes In Bd-summarymentioning
confidence: 55%
“…and reduced presence of IgA-coated Erysipelotrichaceae spp. in the Dutch BD cohort compared to healthy controls, although this was not analyzed in the Italian cohort (14). These data support the requirement for more, larger studies to determine the geographical and environmental changes compared to disease-induced changes in the BD gut microbiome.…”
Section: Gut and Oral Microbiomes In Bd-summarymentioning
confidence: 55%
“…Many researchers expect that microbiota can explain differences in the incidence of BD under various environmental conditions of different regions. Dysbiosis of the gut microbiome may trigger or exacerbate the inflammatory process in BD, and a reduced intestinal microbial diversity was observed in patients with BD ( 27 ). In an animal study, fecal microbiota transplantation using feces from BD patients has been shown to significantly exacerbate uveitis ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…This occurs when dysbiosis of the established microbial community results in inflammation and a decrease in host pathogen resistance. Numerous microbiome studies have established the aetiopathogenesis of diseases (36,38,39,(74)(75)(76).…”
Section: Salivary Microbiomementioning
confidence: 99%
“…Elevated abundances of Dethiosulfovibrionaceae and Spirochaetaceae families, with Trepenema TG5 at genus level being found in the oral microbiome from BD patient (38). Changes in microbiome profile modifying immune responses contribute to immune dysregulation during the development and progression of the diseases (38,41,42). These studies of the salivary microbiome provide information which may assist in the development of new therapies for use in BD (15,38,(40)(41)(42) (Figure 1).…”
Section: Salivary Microbiomementioning
confidence: 99%
See 1 more Smart Citation